1,2,4,5-Tetrafluoro-3,6-diiodobenzene-2,3-bis(pyridin-2-yl)pyrazine (1/1) - Arman, H.D.; Kaulgud, T.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The components of the title 1:1 co-crystal, C14H10N4 center dot C6F4I2, are connected via an N center dot center dot center dot I [2.959 (4) angstrom] halogen bond, in which the N atom is part of the relatively electron-rich pyrazine ring. The C6F4I2 molecule is almost planar [r.m.s. deviation = 0.038 angstrom] but there are significant twists in the pyrazine derivative, as seen in the dihedral angles [31.3 (2) and 54.6 (2)degrees] formed between the pendant pyridyl rings and the central pyrazine ring. The bimolecular aggregates are sustained in the crystal by C-H center dot center dot center dot F and pi-pi interactions [ring centroid(pyridyl)-ring centroid(benzene) = 3.678 (3) angstrom].